ESP Reading in the Context of Learning - Coronel, Rolando Edgardo; Liendo, Nelly Tapia; Diaz, Norma Yolanda (The ESPecialist, 2012)
The pedagogical implications of facing the teaching of reading in ESP through the text-based, the data-based or the interactive approaches have already been the source of many discussions. Apparently the interactive approach, i.e. a combination of the first two, has been unquestionably adopted by ESP practitioners. The purpose of the present work is to analyse, within the framework of a current renewal of interest in foreign language reading, which mode of ESP reading is first selected by ESP students in technical and scientific academic settings from the stand of the learner-centred approach. This report contains the results of tests applied to students of computing and the subsequent analysis.